Prawny, polityczny, filozoficzny i religijny wymiar procesu i stracenia Sokratesa - Kostas E., Beys (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2010)
The article deals with the legal, political, philosophical and religious dimensions of Socrates’ trial and execution. It considers the issue in five separate aspects: 1) the validity of charging Socrates with impiety and corrupting the youth of the Athens; 2) the legal basis of the philosopher’s indictment; 3) the then manner of conducting a legal trial in the Athens; 4) the extent to which Socrates’ conviction can ultimately be characterized as unjust and — finally — 5) the cultural ramifications of the philosopher’s trial and execution.
Keywords: Socrates; Charges of impiety and corrupting the youth; Athenian legal system